Prescription Opioid Use for Acute Pain and Persistent Opioid Use After Gynecologic Surgery: A Systematic Review. Issue 4 (9th April 2023) - Matteson, Kristen A.; Schimpf, Megan O.; Jeppson, Peter C.; Thompson, Jennifer C.; Gala, Rajiv B.; Balgobin, Sunil; Gupta, Ankita; Hobson, Deslyn; Olivera, Cedric; Singh, Ruchira; White, Amanda B.; Balk, Ethan M.; et al.
Abstract : On average, patients use 15 or fewer 5-mg oxycodone tablets (or equivalent) in the 2 weeks after discharge for major gynecologic surgery for benign indications. Abstract : OBJECTIVE: To assess the amount of opioid medication used by patients and the prevalence of persistent opioid use after discharge for gynecologic surgery for benign indications. DATA SOURCES: We systematically searched MEDLINE, EMBASE, and ClinicalTrials.gov from inception to October 2020. METHODS OF STUDY SELECTION: Studies with data on gynecologic surgical procedures for benign indications and the amount of outpatient opioids consumed, or the incidence of either persistent opioid use or opioid-use disorder postsurgery were included. Two reviewers independently screened citations and extracted data from eligible studies. TABULATION, INTEGRATION, AND RESULTS: Thirty-six studies (37 articles) met inclusion criteria. Data were extracted from 35 studies; 23 studies included data on opioids consumed after hospital discharge, and 12 studies included data on persistent opioid use after gynecologic surgery. Average morphine milligram equivalents (MME) used in the 14 days after discharge were 54.0 (95% CI 39.9–68.0, seven tablets of 5-mg oxycodone) across all gynecologic surgery types, 35.0 (95% CI 0–75.12, 4.5 tablets of 5-mg oxycodone) after a vaginal hysterectomy, 59.5 (95% CI 44.4–74.6, eight tablets of 5-mg oxycodone) after laparoscopic hysterectomy, and 108.1 (95% CI 80.5–135.8, 14.5 tablets of 5-mg oxycodone) after abdominal hysterectomy. Patients used 22.4 MME (95% CI 12.4–32.3, three tablets of 5-mg oxycodone) within 24 hours of discharge after laparoscopic procedures without hysterectomy and 79.8 MME (95% CI 37.1–122.6, 10.5 tablets of 5-mg oxycodone) from discharge to 7 or 14 days postdischarge after surgery for prolapse. Persistent opioid use occurred in about 4.4% of patients after gynecologic surgery, but this outcome had high heterogeneity due to variation in populations and definitions of the outcome. CONCLUSION: On average, patients use the equivalent of 15 or fewer 5-mg oxycodone tablets (or equivalent) in the 2 weeks after discharge after major gynecologic surgery for benign indications. Persistent opioid use occurred in 4.4% of patients who underwent gynecologic surgery for benign indications. Our findings could help surgeons minimize overprescribing and reduce medication diversion or misuse. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42020146120.